TUBERCULOSIS MENINGITIS IN CHILDREN AND ADOLESCENTS - G. A. Kharchenko; O. G. Kimirilova; O. N. Chabanova (Туберкулез и болезни лёгких, 2017)
The article presents the clinical and epidemiological data on tuberculosis meningitis among children in Astrakhan Region. It was found out that among those cases 77.8% were children under 7 years old exposed to tuberculosis in their families, meningitis developed against the background of active respiratory tuberculosis and only 17.4% had post-vaccinal scar out of 85.2% who had BCG vaccination. There were two clinical forms of tuberculosis meningitis: basilar form in 59.2% and meningoencephalitis in 40.8% of patients. Late diagnostics and untimely start of treatment were observed in 88.9% of patients.